Pengaruh Sales Promotion Dan Shopping Life Style Terhadap Impulsive Buying Dengan Positive Emotion Variabel Intervening Di Tokopedia - Putri, Aprila; Wijayanto, Gatot; Noviasari, Henni; Andreas Siregar, Prima (Bahtera Inovasi, 2024)
E-commerce has experienced rapid growth in recent years, one of which is Tokopedia and has a significant role in influencing purchasing decisions. The growth of e-commerce has made marketers strengthen their marketing strategies with Sales Promotion which can encourage consumers to make impulse buying decisions also influenced by Shopping Lifestyle and Positive Emotion plays a significant role as a mediator. The purpose of this study was to analyze the effect of Sales Promotion and Shopping Lifestyle on Impulsive Buying which is influenced by Positive Emotion at Tokopedia. This research method uses a quantitative approach with descriptive analysis method. The questionnaire was distributed to 385 respondents using Purposive Sampling technique and processed using Structural Eqquation Modeling - Partial Least Squre with SmartPls software version 4.0.9. The results of this study indicate that Sales Promotion, Shopping Lifestyle, Impulsive Buying, and Positive Emotions affect each other.